Biological Activity and Solubility of 5-Methoxy-1,4-Benzoquinone Having Bromoheptyl and Bromodecyl Substituents in the n-Octanol/Water System - Ulfa, Siti Mariyah; Dwisari, Fath; Pangesti, Laras; Rahman, Mohammad Farid (Makara Journal of Science, 2021)
The biological activity and solubility of compounds are influenced by its chemical structure. These properties can be improved by substituting alkyl, alkoxy, and/or haloalkane in the parent skeleton. In this research, the synthesis of 3-(7-bromoheptyl)-2-methyl-5-methoxy-1,4-benzoquinone (3a) and 3-(10-bromodecyl)-2-methyl-5-methoxy-1,4-benzoquinone (3b) was achieved through the decarboxylation reaction. The solubility and biological activity of 3a and 3b were compared with that of thymoquinone (TQ), which acts as an anti-inflammatory agent. Compounds 3a and 3b were successfully synthesized and analyzed using Fourier Transform Infra-Red (FTIR) and Nuclear Magnetic Resonance (NMR). The FTIR spectrum showed the increasing intensity of C-H sp3 and the absorption of C-Br because of the presence of the bromoheptyl and bromodecyl substituents. 1H-NMR showed the prominent chemical shift of olefinic methylene at δ 1.29–3.40 ppm. The solubility test showed the differences in the partition coefficient (log P) of 3a and 3b in the n-octanol/water system. The log P values of 3a and 3b are higher than those of TQ, indicating that methoxy, bromoheptyl, and bromodecyl support the increase in solubility. Biological activity test using the in silico approach showed that 3a and 3b have a higher tendency to bind with the translocator protein (TSPO) macromolecule than the phosphatase and tensin homolog (PTEN) macromolecule. The binding interactions of TSPO-3a and TSPO-3b, similar to that of TSPO-TQ, showed that both synthesized compounds have comparable activity. The binding energy of TSPO-3a is lower than that of TSPO-3b, indicating that 3a has a higher activity for anti-inflammatory drug candidates than 3b.